2002
DOI: 10.1016/s0960-9822(02)01165-x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of a Meiotic Checkpoint during Drosophila Oogenesis Regulates the Translation of Gurken through Chk2/Mnk

Abstract: DmChk2 is a transducer of the meiotic checkpoint in flies that is activated by unrepaired double-strand DNA breaks. Activation of DmChk2 in this specific checkpoint affects a cell cycle regulator as well as mRNA translation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
143
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(152 citation statements)
references
References 44 publications
6
143
2
Order By: Relevance
“…In particular, the pachytene checkpoint is triggered in meiocytes impaired in synapsis and recombination (Roeder and Bailis, 2000). It widely exists in many species, including S. cerevisiae, Drosophila, C. elegans, and mice, and leads to cell cycle arrest during the pachytene stage and cell death thereafter (Edelmann et al, 1996;McKee and Kleckner, 1997b;Pittman et al, 1998;Gartner et al, 2000;Roeder and Bailis, 2000;Abdu et al, 2002).…”
Section: Mof Is Required For Meiotic Progression In Ricementioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the pachytene checkpoint is triggered in meiocytes impaired in synapsis and recombination (Roeder and Bailis, 2000). It widely exists in many species, including S. cerevisiae, Drosophila, C. elegans, and mice, and leads to cell cycle arrest during the pachytene stage and cell death thereafter (Edelmann et al, 1996;McKee and Kleckner, 1997b;Pittman et al, 1998;Gartner et al, 2000;Roeder and Bailis, 2000;Abdu et al, 2002).…”
Section: Mof Is Required For Meiotic Progression In Ricementioning
confidence: 99%
“…Activation of the pachytene checkpoint leads to an arrest of the meiotic program that results in apoptosis. The pachytene checkpoint widely exists in yeast and animals, including Saccharomyces cerevisiae, Drosophila melanogaster, Caenorhabditis elegans, mice, and other mammals (Edelmann et al, 1996;McKee and Kleckner, 1997b;Pittman et al, 1998;Gartner et al, 2000;Abdu et al, 2002). However, it is not clear whether a similar pachytene checkpoint exists in plants because unlike yeast and animals that cause meiotic cell arrest or cell death, most plant meiotic mutants defective in SPO11 initiated recombination can complete meiosis but produce abnormal microspores Wijnker and Schnittger, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Delays in meiotic DSB repair lead to oocyte dorsal-ventral polarity defects in the developing embryos of females due to the meiotic DSB repair checkpoint (Ghabrial and Schupbach 1999;Abdu et al 2002). We reasoned that if DSB repair occurs by NHEJ in mei-218; spn-D and mei-218; spn-B females, then the frequency of abnormal embryos (a readout for checkpoint activity) laid by these mothers would be reduced.…”
Section: Repair Of Dsbs In Mei-218; Spn-d Depends On Ligase4mentioning
confidence: 99%
“…Later work showed that vas-null females produce rare tumorous egg chambers in which nurse cells and oocytes have not differentiated, and also rare egg chambers with supernumerary, misplaced, or no oocytes, suggesting that Vas may also function in restricting cell fate during germline stem cell (GSC) differentiation (Styhler et al 1998;Tomancak et al 1998). A DNA damage checkpoint that functions in the oocyte during meiotic prophase, after the 16-cell cyst has formed, regulates Vas activity (Ghabrial and Schü pbach 1999;Abdu et al 2002;Findley et al 2003;Theurkauf et al 2006;Chen et al 2007;Pane et al 2007). Vas binds to eIF5B, an essential translation initiation factor that functions in ribosomal subunit joining (Carrera et al 2000;Pestova et al 2000).…”
mentioning
confidence: 99%